Constantinople in Imperial Ideology of Stefan Dušan - Pejušković, Vojislav D. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The centuries-old expansion of the Serbian state at the expense of Byzantium received its epilogue with the rule of Stefan Dušan. The Serbian king managed to use the opportunity provided by the Roman civil war of 1341–1347, manoeuvring between two warring houses, Kantakouzenos and Palaiologos. It was the weakening of both Byzantium and Bulgaria that gave him the opportunity to, by crowning himself emperor of the Serbs and Romans, plan a possible attack on Constantinople, which would absolutely justify the title he had held since 1345. Byzantine sources testify in their own way about Dušan’s negotiations with the Ottomans, Venice and others and the gathering of the coalition against the winner of the civil war—John Kantakouzenos, whose revitalization of Constantinople-controlled territory stood in the way of the Serbian Roman ruler’s imperial ambitions. The testimonies of Nicephorus Gregoras, the emperor-writer himself, as well as the documentary material, led us to the conclusion that Stefan Dušan planned an extensive action directed towards the walls of Theodosius II. Taking into account the data on the order of Empress Anna of Savoy to renew the Thessaloniki fortification elements from 1355/56, it speaks of a possible general attack by the Serbian army. In addition to the above, the place of the emperor’s death, which can still be debated in science, leaves room for various premises since two Ragusian historians wrote that Dušan died in Thrace–in Byzantine territory.